2012
DOI: 10.1007/s12306-012-0222-3
|View full text |Cite
|
Sign up to set email alerts
|

Simple reproducible technique in treatment for osteopetrotic fractures

Abstract: Osteopetrosis is a rare skeletal condition first described by German radiologist Heinrich Albers-Schonberg. The most important technical difficulty is drilling due to hard bone in patients with osteopetrosis; recommendations have been made to use high-speed electric drill bits. But, the unavailability of this special drill bit in most of the centres makes the job more difficult. The study was conducted from 2009 to 2012; the cases are selected from Outpatients Department of Postgraduate Institute of Medical Ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 10 publications
1
16
0
Order By: Relevance
“…Out of these 5 patients there were 4 males and 1 female with a M:F ratio of 1:0.25. This was similar to male preponderance seen in our study [15] . The most common age group affected was found to be 31-35 years followed by in our study followed by 26-30 years.…”
Section: Discussionsupporting
confidence: 92%
“…Out of these 5 patients there were 4 males and 1 female with a M:F ratio of 1:0.25. This was similar to male preponderance seen in our study [15] . The most common age group affected was found to be 31-35 years followed by in our study followed by 26-30 years.…”
Section: Discussionsupporting
confidence: 92%
“…Sen et al recommended using a metal-cutting drill bit to overcome the problem of drill bit breakage. Thus, the drilling was easier and thermal necrosis was prevented 7. Both these studies stated that extra care must be shown to prevent the breakage of drill bits 6,7…”
Section: Discussionmentioning
confidence: 99%
“…Although some authors reported excellent outcomes of the plate-screw system, revision surgery due to implant failure was required in several cases [6, 11, 20–28]. There was also an attempt to prevent implant failure through an augmented technique of osteosynthesis with the plate-screw system [7, 25]. Kulkarni et al [21] reported a 22-year-old male case of ADO type II with the left femoral shaft fracture and a 47-year-old male case of ADO type II with the right subtrochanteric fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Technical difficulties include bending of drill bits or screws during surgery using drilling or carving due to hard-fragile sclerotic bones and a narrow medullary canal. Slow-speed high-torque electric drills, as well as frequent cooling with physiological saline, clearance of drill grooves, and the use of staggered drill system, have been recommended [12, 17, 25]. However, there is still an increased risk of implant failure and nonunion for internal fixation [12, 17].…”
Section: Discussionmentioning
confidence: 99%